Lower Devonian and Lower Carboniferous Conodonts in the Pebbles of the Lower Permian Conglomerate at Podlipoglav, east of Ljubljana, Yugoslavia - Ramovš, Anton (Geologija, 1988)
In the Lower Permian conglomerate, north of Podlipoglav, east of Ljubljana, Slovenia, blocks (olistolites) and pebbles of the Upper Silurian, Lower Devonian and Middle Carboniferous limestones with different fossil groups have been discovered and investigated since 1954. In recent investigations of the conodonts from the pebbles, the Lower Devonian have been established. These results show that in the Lower Devonian and Lower Carboniferous times similar development prevailed in the Ljubljana surroundings as in the Karavanke Mountains.